Social relations in crowds: Recognition, validation and solidarity - Hopkins N.; Reicher S.; Stevenson C.; Pandey K.; Shankar S.; Tewari S. (My University, 2025)
Social identity research on crowds demonstrates how cognitive self-definition as a crowd member results in conformity to identity-relevant norms. Rather less research has addressed the social-relational changes within a crowd and how these impact collective experience positively. The present study investigates these processes at a month-long mass gathering in India. Analysis of 37 interviews with participants attending the annual Magh Mela pilgrimage evidences the concept of shared identity as underpinning their understanding of this mass gathering. Moreover, a theoretically derived thematic analysis of these interviews shows the value of the analytic concepts of recognition, validation, and solidarity in illuminating the ways in which social relations in the crowd were experienced and contributed to the experience of the event. Through exploring the multi-dimensional nature of relational connectedness in crowds we contribute to an understanding of crowd experience and group processes. © 2019 John Wiley & Sons, Ltd.